Assessment of genetic diversity in Ziziphus jujube Mill. Cultivars derived from northern China using inter‐simple sequence repeat markers. Issue 1 (9th March 2020) - Shen, Jie; Sun, Zhaoxia; Hou, Siyu; Liu, Ronghua; Wang, Yuguo; Guo, Pingyi
Abstract: There are abundant germplasm resources for Chinese jujube ( Ziziphus jujuba Mill.), particularly in northern China. This study intended to assess the relationships and genetic structure of 48 cultivars of jujube derived from seven geographical regions in northern China using inter‐simple sequence repeat (ISSR) markers. Eight ISSR primers were selected for determining the genetic diversity of the 48 jujube cultivars, resulting in the amplification of 110 polymorphic bands. The average number of polymorphic bands for the ISSR primers was 13.8 and percentage of polymorphic bands was 86.8%. By analysis of the population genetic structure, the 48 cultivars were classified into two groups, with two homogeneous gene pools according to a Bayesian method. One group was comprised of cultivars from Central Shanxi, Shandong, Hebei, and Henan, while the other group included cultivars from southern Shanxi, Beijing, Shaanxi, Gansu, Shandong, Hebei, and Henan. Unweighted pair‐group method with arithmetic means cluster analysis also indicated two groups with similarity coefficients ranging from .58–.93. In some subgroups, there was a correlation between the genetic relationships among cultivars and their origins, but no relationship between genetic relatedness and cultivar uses. Analysis of molecular variance revealed that 88% of the genetic variation was attributable to variation within populations. Our results provide a considerable amount of polymorphism data in 48 Chinese jujube cultivars, which may serve as a good foundation for further analysis of the correlations between phenotypic and genetic data in Chinese jujube.